The Role of the Antioxidants Lycopene and Vitamin E in the Prevention of Halothane-Induced Hepatotoxicity - Bestas, Azize; Kahramanoglu, Mithat; Erhan, Omer Lutfi; Bolat, Esef; Ozercan, Ibrahim; Gursu, Ferit; Gulcu, Funda (Prous Science, Sau-Thomson Reuters, 2008)
The aim of this study was to examine the effects of lycopene and vitamin E on halothane-induced hepatotoxicity. Thirty-five male albino Wistar rats were studied. The control group (group C) did not receive any treatment. Rats in group H were exposed to 1.5% halothane (in 50% oxygen/50% air) for 2 h on days 10 and 13. Group L received 25 mg/kg/day lycopene, group E received 100 IU/kg/day vitamin E and group LE received lycopene and vitamin E for 13 days. Similar to group H, groups L, E and LE were exposed to halothane. Total antioxidant capacity (TAC), total oxidant level (TOL) and sulfhydryl=thiol groups (SH) were measured. Histopathological examinations were carried out using light microscopy, and histopathological findings were graded on a scale of 0-6. There were no significant differences among the groups in TAC, TOL and SH values (P > 0.05). Liver injury was observed in the four treatment groups; the mean degree of damage was more severe in group H compared to groups E, L and LE: 2.14 +/- 0.37, 1.50 +/- 0.54, 0.85 +/- 0.69 and 0.83 +/- 0.75, respectively This study found that both lycopene and vitamin E reduce holothane-induced hepatotoxicity, although the effect of vitamin E was not statistically significant.
Keywords: Hepatotoxicity; Halothane; Antioxidants; Lycopene; Vitamin E